A contemporary handbook for weddings & funerals and other occasions - Malphurs, Aubrey; Willhite, Keith; Willhite, Keith, 1958- (Grand Rapids, Mich. : Kregel Pubs., 2003)
A compilation of tested ideas and resources by pastors, this handbook provides just the tool pastors need. Written by experienced, familiar authors, this book deals with difficult situations, like the death of a child and second marriages.
pt. 1. Weddings. Traditional wedding services -- Other celebrations of marriage -- Meaningful wedding messages -- The vows of commitment -- Additional help for officiates -- Potpourri for the bride and groom -- pt. 2. Funerals Traditional funeral services -- When death is untimely or unexpected -- Funeral services by family members -- Perspectives on death and dying -- pt. 3. Other occasiions. The Lord's table -- Child or family dedication -- Baptism -- Christmas -- Ordination and installation -- State of the church message -- Reenactment of an influential Christian.
Includes bibliographical references (pages 378-379) and index.
Keywords: Marriage service -- Handbooks, manuals, etc; Funeral service -- Handbooks, manuals, etc; Occasional services/Pastoral Help -- Handbooks, manuals, etc; Handbooks and manuals